KONSTRUKSI REALITAS MEDIA: ANALISIS FRAMING PEMBERITAAN PENYANDERAAN PILOT SUSI AIR DI CNN INDONESIA DAN TRIBUNNEWS - Amin, Nur Auwaliyah; Febrianita, Roziana (Ilmu Komunikasi, FISIP Universitas Pasundan, 2024)
This study discusses the news framing analysis of the hijacking of the Susi Air Pilot in online media outlets CNN Indonesia and Tribunnews from February 2023 to July 31, 2023. The paradigm employed in this research is the constructivist paradigm, utilizing Robert N. Entman's framing analysis method with techniques such as define problems, diagnose causes, make moral judgments, and treatment recommendations. The findings indicate divergent framings between CNN Indonesia and Tribunnews. CNN Indonesia criticizes the military-related strategies of the Indonesian National Armed Forces (TNI) and expresses concerns about the safety of hostages and civilians in Papua, advocating for negotiation as a resolution. In contrast, Tribunnews highlights various issues, viewing the hijacking as a separatist threat and a disruption to domestic and geopolitical political stability. Tribunnews also presents the perspective of the authorities, appearing to align with the government.